Efficiency of a dexamethasone nanosuspension as an intratympanic injection for acute hearing loss - So-Young Jung; Subin Kim; Zion Kang; Soonmin Kwon; Juhye Lee; Joo Won Park; Kab Sig Kim; Dong-Kee Kim (Taylor & Francis Group, 2022)
Dexamethasone sodium phosphate (Dex-SP) is the most commonly used drug administered via intratympanic injection for the treatment of acute hearing loss, but its penetration efficiency into the inner ear is very low. To address this problem, we evaluated the possibility of administering dexamethasone nanosuspensions via intratympanic injection because hydrophobic drugs might be more effective in penetrating the inner ear. Three types of dexamethasone nanosuspensions were prepared; the dexamethasone nanoparticles in the three nanosuspensions were between approximately 250 and 350 nm in size. To compare the efficiency of Dex-SP and dexamethasone nanosuspension in delivering dexamethasone to the inner ear, the concentrations of dexamethasone in perilymph and cochlear tissues were compared by liquid chromatography-mass spectrometry. The dexamethasone nanosuspensions resulted in significantly higher drug concentrations in perilymph and cochlear tissues than Dex-SP at 6 h; interestingly, animals treated with nanosuspensions showed a 26-fold higher dexamethasone concentrations in their cochlear tissues than animals treated with Dex-SP. In addition, dexamethasone nanosuspension caused better glucocorticoid receptor phosphorylation than Dex-SP both in vitro and in vivo, and in the ototoxic animal model, the nanosuspension showed a significantly better hearing-protective effect against ototoxic drugs than Dex-SP. In the in vivo safety evaluation, the nanosuspension showed no toxicity at concentrations up to 20 mg/mL. In conclusion, a nanosuspension of dexamethasone was able to deliver dexamethasone to the cochlea very safely and efficiently and showed potential as a formula for intratympanic injection.